Theory and practice in M&A valuations. Issue 6 (13th June 2016) - Mazzariol, Patrick; Thomas, Mark
Abstract : Purpose: Academics and practitioners are in relative agreement on what drives a company's fundamental value, primarily it's current assets and future cash flows. The practice of paying a premium may thus be due to the non-tangible factors associated with perceived value that currently are not incorporated into the assets of the company and the expected growth of the cash flows. Design/methodology/approach: This paper looks at the most common theoretical models used in the calculation of the value of a firm. It then explains how human factors can cause divergence in the original price set. Findings: Empirical evidence proves that the price paid for a company can easily reach 40-50 per cent above this calculation of the current value. Until valuation models can account for the factors that drive premium pricing, it is necessary to recognize that intangible and, in some cases, emotional aspects will have a great influence on the final price. Practical implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.